Digital Media Utilization Among Pregnant Women In Garut Regency, Indonesia - Helen Frieda Katherine; Restuning Widiasih Widiasih; Witdiawati Witdiawati Witdiawati (Malahayati Nursing Journal, 2026)
ABSTRACT The use of digital media as a source of health information has increased along with the rapid expansion of internet access in Indonesia. Pregnant women are among the population groups that frequently seek health-related information through digital platforms. However, empirical evidence describing how pregnant women utilize digital media for health information at the district level remains limited, particularly in areas with diverse geographic characteristics such as Garut Regency. This study aimed to describe digital media utilization among pregnant women in Garut Regency. A quantitative descriptive study using secondary data from the Ultralight Project (2024). A total of 355 pregnant women were included in the study using total sampling. Data were analyzed using univariate analysis and presented as frequencies and percentages. Pregnant women used various digital media sources, mainly search engines and video-based media. Digital media were used for maternal health information, fetal monitoring, or both. The intensity of use varied from limited to regular weekly use. Pregnant women in Garut Regency use digital media as part of health information-seeking behavior during pregnancy. Digital media function as supportive sources of maternal and fetal health information. Keywords: Digital Media, Health Information Seeking, Maternal Health, Mobile Health Application, Pregnancy.